ANALISIS KONSUMSI PANGAN KOTA PONTIANAK - Erlinda Yurisinthae, Ryafal Akbar Novira Kusrini (Jurnal Social Economic of Agriculture, 2014)
Pontianak city is included in the food secure category ( category 5 ). However, based on observations in the field there are some subdistrict in Pontianak has not shown particularly in food secure access to food when viewed from the quality of food consumption in the form of economic, educational and cultural. This study aims to determine the level of diversity Dietary Pattern Hope ( PPH ) in Pontianak and determine the adequacy of energy and protein levels in Pontianak. The method used in this study are located on the survey method Pontianak. Sampling of this research is to use nonprobability sampling method with purposive sampling with a sample size of 100 respondents consisted of 58 respondents in North Pontianak Pontianak and 42 respondents in the East. Data analysis using food recall method is based on a 24-hour consumption of food and the amount generally consumed by individuals in a day or so on certain days. The results showed that the level of diversity Dietary Pattern Hope ( PPH ) in Pontianak is equal to 83.5 yet reached the ideal is equal to 100. Moreover, the adequacy and sufficiency level of energy and protein in Pontianak City in general has been good in the amount of 1,874 kcal / hood / day or and 52 g / person / day. In the area of ​​fisheries adequacy of energy and protein levels have been good in 2013 kcal / person / day and 52 g / person / day, while the adequacy of the level of agricultural areas have good energy 1773 kcal / person / day but do not meet the adequacy standard, while 52 grams of protein is good / person / day. Keywords :      Food Consumption, Dietary Pattern Hope, Adequacy of Energy, Protein Adequacy.